Scrutinizing Middle School Teachers’ Knowledge and Perception on the Integration of Science and Religion - Elbina Mamla Sa'idah; Murhayati Sri; Edison Edison (AL-ISHLAH: Jurnal Pendidikan, 2023)
Discussion about the integration between science and religion is no longer a new topic, but nowadays it is being raised again. Many researchers believe that both of them are independent entities, but many researchers also argue that there is potential for combining the two. This study aimed to investigate the knowledge and skills as well as the perception of teachers on how to integrate science and religion. This qualitative study was conducted in Bengkalis Regency. Thirty-one in-service teachers from four different junior high schools were recruited as the participants of this study. The data were collected by administering open ended questionnaires and interviews to the participants. To analyze the data, the researcher used the three stages in qualitative data analysis, namely data reduction, data verification, and data display. The findings reported that teachers’ competence on the integration of science and religion is quite good and comprehensive because they were able to explain the importance of this integration and how to implement the combination of the two in their own area of teaching subjects, even develop the teaching materials as the implication for the practice in junior high school contexts. However, the findings also indicated the drawbacks of some teachers who found the difficulties in applying the science-religion integration in the subjects due to several reasons. In conclusion, combining science and religion is not an impossible action as long as teachers have a strong belief, wide knowledge, and a harmonious view between the two, also the ability to apply it. Therefore, equipping teachers with knowledge and skills through particular training is really crucial.